PENERAPAN MESIN PENGADUK PADA UKM OLAHAN WALUH DI KECAMATAN GETASAN KABUPATEN SEMARANG - Sunyoto Sunyoto; Atiek Zahrulianingdyah; Rosidah Rosidah; Indah Anisykulillah (Jurnal Ilmiah Teknosains, 2020)
The aim of this activity is to solve the problems faced by SMEs engaged in processing pumpkin  as a superior product of Semarang Regency, Central Java. As an activity partner is UKM "KARUNA" led by Mrs. Nanik with the address of Getasan Village, Getasan District, Kab. Semarang. The main product of SME partners is geplak waluh (as snack). The process of making geplak waluh goes through several steps, and the most burdensome stage is the stirring process which takes a long time (8 hours) and is done manually. To overcome this problem, the implementation team has designed appropriate technology in the form of a geplak waluh mixer. The activity method includes several stages, including problem analysis, concept design, drawing work, component manufacturing, assembly, machine testing, and machine refinement. This activity has succeeded in implementing a geplak pumpkin mixer with 1 HP electric motor, 23.33 RPM stirring blade rotation, 24 kg production capacity, 5 hours cooking process. Thus the application of this machine can save 3 hours of time (37,5%), better product quality, more hygienic, and relieve workers